L'abus de pouvoirs en droit administratif canadien et québécois - Gagnon, Jean (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1978)
In the exercise of their functions, administrative authorities may happen to abuse their powers. The courts may then interfere. Judicial review of administrative action may be styled « objective » or « subjective ». In the first case, one ascertains whether the action under review keeps within the law. In the second, the test refers to the aims of the enabling legislation. Of course, the efficency of the latter type of review depends on the scope of the discretion delegated to the administrative authority : as the scope of discretion widens, opportunities for review narrow down. Moreover, review may be made difficult where the administrative authority is not compelled by law to give reasons for its decisions and also where the aims sought by the delegating legislature are not crystal clear. Courts may set aside administrative decisions based on irrelevant grounds or taken in bad faith. In other words, want of public interest justifies judicial intervention, even in the face of privative clauses. Courts may also consider the reasonableness of administrative action, and quash rulings which are discriminatory or arrived at without justification.